Optimising Community-Based Forest Management Policy In Indonesia: A Critical Review - Lucas Rumboko; Digby Race; Allan Curtis (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
Community-based forest management (CBFM) is a popular concept in many countries, covering over 400 million hectares worldwide. In Indonesia, CBFM is viewed as an important component of the forestry sector with the government’s goal to establish 5.6 million hectares of CBFM by 2011 (twice the area of industrial plantation forests). The Indonesian government is pursuing CBFM as a strategy to reduce deforestation of tropical forests, to alleviate poverty in rural communities, and to contribute timber supplies to the processing industry.There has been a belief that CBFM can lead to a physical and socio-economic transformation at the local level. However, in practice, especially in Indonesia, this claim appears problematic because in over 35 years since it has been officially introduced it does not appear to have contributed significantly to address the problems of deforestation and rural poverty.Despite the government’s ambitious goal for CBFM, there are several challenges, for instance the entrenched poverty of many rural communities and inconsistent and unsupportive policies of CBFM at the national, provincial, and local government. This paper is intended to explore, discusses, and criticize the implementation of CBFM policies in various countries and in particular in Indonesia. This paper also aims to explore its challenges in the future development in Indonesia.